BL_GERICHTE 715 22 116 / 83 vom 30. März 2023 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 30. März 2023 (715 22 116 / 83) - BL Gerichte (2023)
Vermittlungsfähigkeit